The scandal as a form of political domination - Arias, Luis Miguel (1995)
The text is not intended to provide solutions to a well-known problem within the guild of political scientists and lawyers. This phenomenon is currently generating, in varying degrees, an extensive intellectual production and a critical reflection, which aims to shed some light on the way and the way of functioning of political systems in this era of dissolution of the old system of management international, after the fall of the wall and the decomposition of the former Eastern Bloc. The accent falls especially on the democratic political systems in the orbit of the Western world where the emergence of certain 'perverse' processes would seem to presage the fact of a deep crisis of the representative systems. Of this they give account the news and reports that appear in the press and in the rest of the means, referred to a series of public scandals.